Analysis and Design of Disease Diagnosis Systems and Patient Medicine Recommendations with Forward Chaining Method - Samuel Ryon Elkana; Verri Kuswanto (bit-Tech, 2023)
Technological developments have had a significant impact on many aspects of life, one of which is patient care in hospitals. Apart from using technology in patient care, technology also provides access to effective and efficient information storage and management to record patient data for treatment purposes. In outpatient services at hospitals, there are often complaints from employees regarding the health recording system which is less than optimal. Therefore, a system that manages disease diagnoses and patient treatment recommendations is something that needs to be developed, with the hope of speeding up the performance of medical personnel, so that they can help more patients who need help. The application system design aims to help manage information related to disease diagnosis and patient drug recommendations, where this system uses Forward Chaining to assist users in identifying diseases and prescribing drugs according to the diagnosis the patient is complaining about. By using the Forward Chaining methodology, medical personnel are able to obtain patient diagnosis results more quickly. The result is an application that can help medical personnel in serving outpatients from registration, examination, to exchanging medicines. This application has been tested using black-box testing involving several respondents, where respondents can feel that this application works well and helps hospital staff in examining patients.